Loss of household income and self- reported health during the covid-19 lockdown in South Africa - Pillay, Cayla (© University of the Witswatersrand, Johannesburg, 2023)
The COVID-19 pandemic struck the world unexpectedly and caused a detrimental economic and health crisis worldwide. Globally, lockdown protocols were implemented to ease the pandemic's initial effects, and South Africa was no exception. This paper provides evidence of the relationship between loss of household income and self-reported health. This study uses a fixed-effects Linear Probability Model (LPM), and the results present a negative relationship between loss of household income and self-reported health. The changes in lockdown levels have no significant effect on loss of income. The outcomes suggest that when income is lost, the health of individuals tends to deteriorate.
A Research Report submitted in partial fulfilment of the Degree of Master of Commerce (Economic Science) in the School of Economics and Finance, University of the Witwatersrand
Keywords: Loss of household income; Self-reported health; Fixed-effects Linear Probability Model (LPM); Lockdown levels; UCTD; SDG-8: Decent work and economic growth; SDG-3: Good health and well-being